2004
DOI: 10.1093/nar/gkh531
|View full text |Cite
|
Sign up to set email alerts
|

Unusual 2-aminopurine fluorescence from a complex of DNA and the EcoKI methyltransferase

Abstract: The methyltransferase, M.EcoKI, recognizes the DNA sequence 5'-AACNNNNNNGTGC-3' and methylates adenine at the underlined positions. DNA methylation has been shown by crystallography to occur via a base flipping mechanism and is believed to be a general mechanism for all methyltransferases. If no structure is available, the fluorescence of 2-aminopurine is often used as a signal for base flipping as it shows enhanced fluorescence when its environment is perturbed. We find that 2-aminopurine gives enhanced fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 47 publications
1
32
0
2
Order By: Relevance
“…Accordingly, dipole-dipole interactions between 2AP and polar solvents will divert energy from 2AP, resulting in red-shifted emission. Blue-shifted emission has also been reported for a 2AP-labeled DNA substrate upon addition of the DNA methyltransferase EcoKI [33].…”
Section: Effect Of Microenvironment On 2ap Lifetime Distributionmentioning
confidence: 75%
See 1 more Smart Citation
“…Accordingly, dipole-dipole interactions between 2AP and polar solvents will divert energy from 2AP, resulting in red-shifted emission. Blue-shifted emission has also been reported for a 2AP-labeled DNA substrate upon addition of the DNA methyltransferase EcoKI [33].…”
Section: Effect Of Microenvironment On 2ap Lifetime Distributionmentioning
confidence: 75%
“…Furthermore, the large FWHM value for 2AP measured at the shorter wavelength ( Figure 8) is consistent with increased heterogeneity of 2AP emission from the F state versus the R state. In previous studies, differences in fluorescence lifetime properties from F versus R states of the single tryptophan residue in staphylococcal nuclease revealed that local intramolecular dynamics create a polar environment around tryptophan rather than exposure to aqueous solvent [33]. Similarly, 2AP intensity decays from F and R states may help to predict the microenvironment around 2AP in different states.…”
Section: Effect Of Spectral Relaxation On 2-ap Lifetime Distributionmentioning
confidence: 97%
“…The annealing efficiency of all duplexes or gapped duplexes (i.e. those with two short oligonucleotides annealed to a single long oligonucleotide) was checked using analytical high-performance liquid chromatography as described elsewhere (6). A molar ratio of 1:1 was obtained for the annealed duplexes and of 1:1:1 for the gapped duplexes, as required.…”
Section: Methodsmentioning
confidence: 99%
“…This communication of methylation status from one adenine target to the other presumably occurs via conformational changes induced by the recognition of the presence or absence of methyl groups on the adenines by the enzyme via steric clashes between the enzyme–S-adenosyl-methionine (SAM) cofactor complex and the DNA (4). It is likely that the methyl group on the cofactor is the sensor for the methyl group on the DNA, and it is highly probable that, in common with all other DNA methyltransferases (5), recognition of adenine methylation requires flipping of the target base out of the DNA helix into the enzyme methylation pocket, where it can interact with the cofactor (6). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, 2AP functions as a probe for interactions between neighboring bases. 2AP has been used to study mispair recognition, [13][14][15] base flipping, [16,17] local melting, [1,6,7] protein binding, [18][19][20] and electron transfer. [21][22][23][24] A four-exponential decay of 2AP fluorescence is often observed in DNA fragments.…”
Section: Introductionmentioning
confidence: 99%